(untitled) (Glocalism: Journal of Culture, Politics and Innovation, 2022)
Under the framework of the Forum of China-Africa Cooperation in the twenty-first century, a growing number of students from the South, especially those from African countries that enjoy strong ties with China, have enrolled themselves in Chinese universities. In China’s higher education sector, their number had grown from 1,384 students in 1999 to 81,562 students in 2018. This study was based on in-depth interviews with 18 African university students that were triangulated with participant observations and a literature review. The participants were interviewed offline and online on social media platforms inside the Internet Firewall of China – such as Microblogs and WeChat – and Facebook from 2019 to 2020. This study aimed to understand how the participants discovered and explored new opportunities in digital entrepreneurship as university students in China. Although engagement in digital entrepreneurship can lead to empowerment and new forms of belongingness, however, new challenges and setbacks can emerge concurrently to disrupt their entrepreneurial trajectory. In terms of opportunities, the participants drew on educational, social and cultural capital to establish their start-ups, but their relative success was challenged by disruptions in the digital ecosystem and the “zero Covid-19” policy in China.